STRENGTHENING NUMERACY AND SCIENCE LITERACY SKILLS BASED ON RELIGIOUS MODERATION - Lessy, Djaffar; Asshagab, Siti Mutiaraningsih; Riaddin, Dinar; Jamdin, Zamrin; Kaliky, Syafruddin (Universitas Labuhanbatu, 2025)
Purpose – This study aims to integrate this concept into the school environment, one way being through learning, which helps students understand and practice the teachings of Islam in a moderate and tolerant manner.Methodology – This research employs a qualitative and descriptive approach, utilizing the Participatory Action Research (PAR) method. The subjects of our Community Service activities consisted of 19 teachers and 39 students from three Madrasah Ibtidaiyah in the Central Maluku district, namely Madrasah Ibtidaiyah Al Hidayah Liang, Madrasah Ibtidaiyah Salman Al Farisi Liang, and Madrasah Ibtidaiyah Al Kahar 2 Iha Liang.Findings – Training on strengthening numeracy literacy and science literacy based on religious moderation can improve the ability of teachers at 3 Madrasah Ibtidaiyah in Central Maluku district to implement numeracy literacy-based mathematics learning and science literacy-based science learning. The pre-test results showed an average score of 27, while the post-test average increased significantly to 75.3. On the other hand, for the application of numeracy literacy learning and science literacy based on religious moderation, there are still teachers who struggle to apply it.Contribution – This research can improve the ability of teachers and students regarding numeracy literacy and science literacy at 3 Madrasah Ibtidaiyah in Central Maluku district, as well as understanding and applying the concept of religious moderation in everyday life.